Văn học Việt Nam thế kỷ XX : Truyện ngắn 1945-1975. Q.2, T.11 - Phan Cự Đệ; Bùi Việt Thắng; Hà Văn Đức; Lý Hoài Thu; Hồ Thu Giang; Nguyễn Thị Hương Giang (Hà Nội : Văn học, 2004)
Võ Huy Tâm; Nguyễn Thị Cẩm Thạnh; Nguyễn Quang Thân; Bùi Bình Thi; Nguyễn Đình Thi; Nguyễn Thi; Xuân Thiều; Bích Thuận.
Keywords: Văn học Việt; Truyện ngắn Việt, -- 1945-1975.